On some Abnormal Leaves of Ginkgo - Vaid, K. M. (Indian Forester, 1971)
Ginkgo biLoba Linn. Bears the normal triangular shaped bi-lobed leaves. In 1920 and afterwards for 12 years Prof. Birbal Sahni collected some abnormal leaves forming funnels and funnel-shaped pockets etc. on the trees growing in Lahore, Mussoorie and Cambridge but never on trees growing in Dehra Dun, Calcutta, Vienna, Dresden. Occurrence of such abnormalities on Ginkgo trees in Dehra Dun is being recorded for the first time, as also some of the reasons for their being so.